The Effectiveness of Make A Match Learning Model on Student Learning Outcomes in the Motion System Material - Dewayani, Rahma Dita; Pukan, Krispinus Kedati; Budi Prasetyo, Andreas Priyono (Journal of Biology Education, 2020)
This study is entitled "The Effectiveness of the Make A Match Learning Model on Student Learning Outcomes on the Motion System Material". The purpose of this study was to examine the effectiveness of the make a match learning model on student learning outcomes. The assessment indicators in this final project include three domains, which are cognitive, affective, and psychomotor learning outcomes. The design of this experimental research is the pretest-posttest control group. The population of this study is all students of class XI MIPA of SMA N 1 Jekulo consisting of 4 classes. The sample of this study is taken by a cluster random sampling technique, where students of class XI MIPA 1 as a control class and students of class XI MIPA 2 as an experimental class. Cognitive learning outcomes data (posttest) are tested, affective learning outcomes (attitudes), psychomotor learning outcomes (skills) and student responses are analyzed in a descriptive qualitative manner. The results show the percentage of classical completeness between the experimental and control classes is 91.66% Ëƒ 62.85%. The attitude of the experimental class students > the control class in each aspect is classified as good and very good with a difference of â‰¤ 10% in the aspects of the discipline, cooperation, confidence, and curiosity. The number of students who are highly skilled in the experimental class and control class is 58.33% Ëƒ 34.29%. Student responses to the application of the make a match learning model 52.77% are very good and 47.77% which is good. The conclusion of this research is the make a match learning model is effectively used in the learning of motion system material in SMA N 1 Jekulo.